Social and Collaborative Businesses: approaches and the potential brought by the Creative Economy - Stephan, Clarisse (Brazilian Journal of Operations & Production Management, 2018)
This paper aims at comprehending the new productive arrangements called social and collaborative business – drawing a parallel between them – and analyzing their potential for success in the market segment that has been called “Creative Economy”. Upon the analysis of such economy, which is characterized for being intensive in immaterial goods (ubiquitous and non-rival), these new productive formats could take root, since taking into account their propagated ethics of democratization, self-management and sharing, their production factors should be, by excellence, not scarce and subject to continuous renewal.